Dihydrotestosterone treatment rescues the decline in protein synthesis as a result of sarcopenia in isolated mouse skeletal muscle fibres. Issue 1 (25th April 2016) - Wendowski, Oskar; Redshaw, Zoe; Mutungi, Gabriel
Abstract: Background: Sarcopenia, the progressive decline in skeletal muscle mass and function with age, is a debilitating condition. It leads to inactivity, falls, and loss of independence. Despite this, its cause(s) and the underlying mechanism(s) are still poorly understood. Methods: In this study, small skeletal muscle fibre bundles isolated from the extensor digitorum longus (a fast‐twitch muscle) and the soleus (a slow‐twitch muscle) of adult mice of different ages (range 100–900 days old) were used to investigate the effects of ageing and dihydrotestosterone (DHT) treatment on protein synthesis as well as the expression and function of two amino acid transporters; the sodium‐coupled neutral amino acid transporter (SNAT) 2, and the sodium‐independent L‐type amino‐acid transporter (LAT) 2. Results: At all ages investigated, protein synthesis was always higher in the slow‐twitch than in the fast‐twitch muscle fibres and decreased with age in both fibre types. However, the decline was greater in the fast‐twitch than in the slow‐twitch fibres and was accompanied by a reduction in the expression of SNAT2 and LAT2 at the protein level. Again, the decrease in the expression of the amino acid transporters was greater in the fast‐twitch than in the slow‐twitch fibres. In contrast, ageing had no effect on SNAT2 and LAT2 expressions at the mRNA level. Treating the muscle fibre bundles with physiological concentrations (~2 nM) of DHT for 1 h completely reversed the effects of ageing on protein synthesis and the expression of SNAT2 and LAT2 protein in both fibre types. Conclusion: From the observations that ageing is accompanied by a reduction in protein synthesis and transporter expression and that these effects are reversed by DHT treatment, we conclude that sarcopenia arises from an age‐dependent reduction in protein synthesis caused, in part, by the lack of or by the low bioavailability of the male sex steroid, DHT.